DETECTING OF CONJUNCTIVAL MICROANGIOPATHY IN CHILDREN AND TEENAGERS WITH TYPE I DIABETES-A NEW PROPOSED APPROACH - Carmen Tiutiuca; Geanina Totolici; Boev Monica; Ana Magdalena Bratu; Dana Tutunaru; Dinu Bogdan Tiutiuca; Ciprian Dinu; Ciprian Florin Badea (Romanian Society of Oral Rehabilitation, 2023)
We demonstrate the efficiency of the conjunctival microcirculation evaluation via the processing technique, the analysis and the imagistic interpretation (using CorelDRAW and MATLAB) of the photos capturing the evolution of the conjunctival microcirculation throughout the course of the disease in children and teens with type 1 diabetes, on a prospective clinical study on a lot of 100 children with type 1 diabetes and values of glucose and glycosylated haemoglobin which illustrate a precarious metabolic control. The analysis through software techniques of the photos capturing the conjunctival circulation in a standardized area led to the elaboration of a numerical description of the pixels distribution providing values which reflect the density of the microvascularization in the corresponding sector. The average value of the black and white pixels was named index of the conjunctival circulation and was used as a tool to emphasise the emergence of the conjunctival microcirculatory modifications which were analysed in relation with the control batch and in correlation with the duration of the disease. In the case of diabetic children, the conjunctival index registered an average value of 450.55 exceeding the value of 250.17 which represents the average value of this parameter in healthy children. There are also significant differences of the conjunctival index depending on the duration of the disease; it displays a continuous increase for a duration of the disease up to 10-11 years, followed by a decrease. The technique proposed might represent a useful method in the surveillance of the conjunctival microcirculation in patients suffering from diabetes. In the study described here, it permitted the highlighting of some early manifestations, identifiable at the level of the conjunctival vessels, modifications which can be attributed to the diabetic disease.